Peranan Jalaluddin Rumi dalam Mendirikan Tarekat Maulawiyah di Konya Tahun 1258-1273 M - Eva Syarifah Wardah; Siti Rohayati (Tsaqofah, 2020)
Jalaluddin Rumi is a teacher, poets, and famous Sufi order which came from Persia. Besides his famous works, Jalaluddin Rumi also founded Tarekat Maulawiyah in the year of 1258 M, based in Konya. Based on history, Tarekat Maulawiyah born since the establishment friendship between Jalaluddin Rumi with this teacher, Syamsuddin At-Tabrizi. Sama’ (spinning dance) from teachings Tarekat Maulawiyah raises pros and cons in the Konya community, because the teachings are considered strange. In developing Tarekat Maulawiyah, Jalaluddin Rumi make efforts like teaching, making Sama’ a basic characteristic Tarekat Maulawiyah, and writing poetry.